GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 206432 species occurrences available in GBIF matching the query: TaxonKey: Bromus hordeaceus L. HasCoordinate: true HasGeospatialIssue: false. The dataset includes 206432 records from 390 constituent datasets: 28 records from Merseyside BioBank (unverified). 2 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 5 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 1940 records from OEH Atlas of NSW Wildlife. 131 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from HUFU - Herbarium Uberlandense. 6 records from Phanerogamic Botanical Collections (S). 10 records from Jordal. 2 records from PRECIS (KwaZulu-Natal Herbarium). 4 records from University of Vienna, Institute for Botany - Herbarium WU. 90 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 67 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 67 records from Online Atlas of vascular plants 2012-2020. 3 records from IAC - Herbário do Instituto Agronômico de Campinas. 184 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 20 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from PlutoF platform observations. 39 records from PRECIS. 1 records from Local BioBlitz Challenge 2013. 4825 records from FLORIVON. 5673 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 8 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 12336 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 3 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 786 records from SA Flora (BDBSA). 82 records from Local Wildlife Site Surveys Berkshire. 31 records from BioFokus. 2 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 91 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 88 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 5232 records from Artdata. 3 records from Flora of Słowiński National Park, Poland. 13 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 3 records from Stabbetorp - Floristiske registreringer 2016. 18 records from InboVeg - NICHE-Vlaanderen groundwater related vegetation relevés for Flanders, Belgium. 1 records from Herbario Museo de La Salle Bogotá (MLS). 3 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 71 records from GenLink - Collected plant samples on grassland EPs. 112 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 1 records from NCC Berkshire Chalk Grassland Survey 1985. 150 records from OHN. 259 records from Données ONF Faune-Flore-Fonge. 964 records from Australia's Virtual Herbarium. 1980 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 68 records from Vascular Plant Herbarium, UiB. 434 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 3 records from Natural History Museum Maastricht (NL) - Herbarium. 2043 records from Consortium of California Herbaria. 69 records from iNaturalist Research-grade Observations. 30 records from CONN. 2 records from Merseyside BioBank Active Naturalists (unverified). 1 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 5 records from Estonian Museum of Natural History. 3 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 2 records from Estonian University of Life Sciences. 75 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 1 records from VFD-H: Rheingau: Pferdeweide Loock. 1 records from Seewasen. 1 records from Küstenschutzwald. 1 records from Kremmer Luch. 1 records from Beweidungsprojekt an der Nesse. 1 records from Flora. 1 records from Grenzturm Hohen Neuendorf. 1 records from Isarufer. 1 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 1 records from Hochschulgelände (Bremen). 1 records from Berlin - Treptower Park / Karpfenteich. 1 records from Kiesgruben Wemb. 1 records from Regenrückhaltebecken (Zeulenroda). 1 records from Deponie Klausdorf. 1 records from Wangerooge. 10 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 1 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 1 records from Ried und Sand - Artenvielfalt durch Beweidung. 1 records from Stever. 1 records from Landschaftsschutzgebiet "Holmer Sandberge". 1 records from Mainufer. 1 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1 records from Ökologischer Weinberg (Guntersblum). 1 records from Trockenrasen Franzigmark (Halle/Saale). 1 records from Tag der Artenvielfalt BUND Kaiserslautern. 1 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 1 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 1 records from Warnowtal (Rostock). 1 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 1 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 1 records from Gieselbachtal Fulda-Harmerz. 1 records from Artenvielfalt auf der Wiese. 1 records from Weidegut Rechab. 1 records from Grillhütte Wettsaasen, Wiese, Hecken. 1 records from Weidewirtschaft. 1 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 1 records from VFD-RP: Taunus: Ponykoppel Thurner. 1 records from Hochschule Zittau/Görlitz. 1 records from VFD-H: Heidenrod: Pferdeweide Mürth. 1 records from Schulgelände Kranich-Gymnasium (Salzgitter). 1 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 1 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 1 records from Sudeniederung (Amt Neuhaus). 1 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 1 records from Rohrmeistereiplateau und angrenzendes Gebiet. 2 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 1 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 2 records from Schulzentrum "Parc Hosingen". 1 records from VFD-RP: Eifel: Orchideenweide Ankly. 1 records from Weinberg Reichersdorf. 1 records from Schatzinsel Wangerooge. 1 records from VFD-HH/SH: Pferdweide Lammert. 1 records from Hettstadt Gehäge. 1 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 1 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 1 records from Streuobstwiese Stedar. 1 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 1 records from VFD-H: Heidenrod: Weide am Ortsrand. 1 records from Pflanzen und Tiere im Burgwald. 1 records from Von der Nutzung zur Natur. 1 records from VFD HH/SH "Pferdeweide Lemsahl". 1 records from VFD-RP: Taunus: Mähweide Dehe. 8142 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 200 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 1 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 1 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 112 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 333 records from naturgucker. 1 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 6 records from English Nature Oxfordshire Chalk Grassland Survey. 26 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from National Trust - Hatfield Forest species data held by The National Trust.. 7 records from English Nature Oxford City Surveys. 2 records from Freiburger GEO-Tag der Artenvielfalt. 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 1 records from Kühmark bei Wetzlar. 1 records from GEO-Hauptveranstaltung in "Wildtierland". 1 records from LBV 100 - Artenvielfalt am Rothsee. 1 records from Bayerische Donau - Leipheim. 1 records from Schatzinsel Norderney. 1 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 212 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 2 records from Butterberg, Dardesheim. 2 records from Bulau. 2 records from Luderbusch. 1 records from Rur. 1 records from Wälder bei Nordkirchen. 1 records from Projekt Dellbrücker Heide. 1 records from Bayerische Donau - Blindheim Donaubrücke. 1 records from Streuobstwiese Stedar 2008. 1 records from Streuobstwiese Stedar 2009. 1 records from Naturpark Sternberger Seenland. 1 records from Pfingstexkursion Alter Bessin. 1 records from Artenvielfalt und Kulturlandschaft. 1 records from Naturschutzgebiet Lüneburger Heide. 38366 records from Dutch Vegetation Database (LVD). 46047 records from INPN - Données flore des CBN agrégées par la FCBN. 42 records from NZ National Vegetation Survey occurrence data. 1 records from BioBlitz Barcelona 2010-14. 1855 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 30 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1 records from Herbario del CIBNOR. 7 records from Vascular plant specimens of Akita Prefectural Museum. 1 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 142 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 1 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 212 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 203 records from Tiroler Landesmuseum Ferdinandeum. 322 records from IBF Monitoring of Vascular Plants. 16 records from Tropicos Specimen Data. 14 records from Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 1523 records from BRERC species records recorded over 15 years ago. 62 records from Natural History Museum (London) Collection Specimens. 145 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 48 records from Natural History Museum, Vienna - Herbarium W. 4 records from Inventario de Flora y Vegetación del Municipio de Enguídanos (Cuenca), 2010. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 404 records from Flora-On: occurrence data of the flora of mainland Portugal. 27 records from Ireland's BioBlitz. 14 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 6 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 27 records from NMNH Extant Specimen and Observation Records. 37 records from Mountain Invasion Research Network (MIREN) survey. 3 records from Canadian Museum of Nature Herbarium. 141 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 1 records from The AAU Herbarium Database. 12 records from Herbarium (ICEL). 7 records from Herbarium (AMNH). 1 records from Observational database of Icelandic plants. 113 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 34 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 99 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 15 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 14 records from Herbario de la Universidad de Almeria. 19 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 74 records from Jardín Botánico de Córdoba: Herbarium COA. 39 records from CIBIO, Alicante:ABH-GBIF. 74 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 37 records from Herbario de la Universidad de Sevilla. 236 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 41 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 30 records from Institut Botanic de Barcelona, BC. 6 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 70 records from Auckland Museum Botany Collection. 28 records from Herbarium of Jyväskylä University Museum. 86 records from Vascular Plant Collection. 23 records from Botany registration database by Danish botanists. 32 records from DAV UC Davis Center for Plant Diversity. 2 records from Herbarium (UNA). 1 records from GEO Biodiversity Day. 15 records from Herbarium Berolinense. 142 records from Herbarium Willing. 9785 records from Observations du Conservatoire botanique national du Bassin parisien.. 68 records from Biologiezentrum Linz. 1 records from United States National Plant Germplasm System Collection. 1 records from The Erysiphales Collection at the University Halle-Wittenberg. 32 records from USU-UTC Specimen Database. 1 records from Institut Botanic de Barcelona, BC-Histórico. 15 records from inatura - Erlebnis Naturschau Dornbirn. 6 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 221 records from Staffordshire Ecological Record - SER Site-based Surveys. 96 records from Biodiversitätsdatenbank des Landes Salzburg. 1 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 2 records from Repatriación de datos del Herbario de Arizona (ARIZ). 2 records from Vascular Plants, Observations, Oslo (O). 89 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from BÜG. 1 records from LaBoOb02. 1 records from Klutensee. 1 records from DJH. 1 records from Naturschutzgebiet Sistig-Krekeler-Heide. 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Kernberge und Umgebung (Jena). 1 records from Mooswald (Freiburg). 1 records from Gemeinde Sursee. 1 records from Naturschutzgebiet Bausenberg. 1 records from Schlern - (Bozen). 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Zukünftiges NSG Höftland/Bockholmwik. 1 records from Königstetten. 1 records from Freiburger Tag der Artenvielfalt. 1 records from Gelände des IVL (Zeckern). 1 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Umgebung der Gesamtschule Hamburg-Winterhude. 1 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 1 records from Philosophenwald und Wieseckaue in Gießen. 1 records from Cuxhavener Küstenheiden. 1 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Danisco-Wiese. 1 records from nazza. 1 records from katzenbuckel. 1 records from Biologische Station im Kreis Wesel. 1 records from GEO-Hauptveranstaltung (Insel Vilm). 1 records from BUND - Dassower See (Lübeck/Dassow). 1 records from Entdeckertour am Muldestausee. 1 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 1 records from Pilstingermoos. 1 records from Artenfülle um das Schalkenmehrener Maar. 1 records from Riedensee. 1 records from 20 Jahre Naturschutzgebiet Dreienberg. 1 records from 4. GEO-Tag in Eberbach. 1 records from Wald am Schloss Wittgenstein Bad Laasphe. 1 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 1 records from Bergbaufolgelandschaft am Muldestausee. 1 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 2 records from Kiesbagger (Mittelhausen). 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from Umgebung der Gesamtschule Winterhude (Hamburg). 1 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 1 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 1 records from Urwald 1 (Bad Waldsee). 1 records from Fuldaaue (Stadtgebiet Fulda). 1 records from Stadtgebiet (Dannenberg). 1 records from Bergkamen- Bergehalde Großes Holz. 1 records from Bizzenbachtal (Wehrheim/Taunus). 1 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 1 records from renaturierter Main (Kemmern bei Bamberg). 1 records from 3. Tag der Artenvielfalt Hockenheim. 1 records from Wupperaue bei Kemna (Wuppertal). 1 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 1 records from Altenburg bei Bamberg. 1 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 1 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Walldorf-Wiesloch: "Natur über den Gleisen". 1 records from Innenstadt Göttingen - Natur Zuhause. 1 records from Naturgarten Langenholtensen. 1 records from Tag der Artenvielfalt. 1 records from Unna-Mühlhausen, Wiesen. 2182 records from Atlas Flora Danica. 156 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 3322 records from Belgian IFBL Flora Checklists (1939-1971). 2811 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 1 records from Perchtoldsdorfer Heide. 1 records from Schwanheimer Wald. 1 records from Freiburger Netzwerk Artenvielfalt. 1 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 1 records from Berkel. 1 records from Tag der Artenvielfalt mit SchülerInnen des Leibniz-Gymnasiums in Neustadt a.d.W.. 1 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 1 records from NSG Haunestausee, Hauneteiche. 1 records from Colorado State University Herbarium. 1 records from Lustadter Wald .. 11 records from R. L. McGregor Herbarium Vascular Plants Collection. 897 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 14 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 14 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 1 records from Artenvielfalt am Schlern. 1 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 1 records from VFD-BW, Dinkelberg: Pferdeweiden Oberminseln. 1 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 1 records from VFD-BW, Schwäbische Alb: Pferdeweiden Zainingen. 1 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 1 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 4 records from Jardín Botánico Atlántico, Gijón: JBAG. 68 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 786 records from Biological and palaeontological collection and observation data MNHNL. 1 records from Botany Division, Yale Peabody Museum. 1 records from VFD-RP, Taunus: Bergweide Dehe. 6 records from Herbarium Senckenbergianum (FR). 17 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 4 records from Herbario de Universidad de Murcia: MUB. 1 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 100 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Wetland Inventory (NV). 1316 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 2 records from National Trust - Sutton Hoo species data held by The National Trust.. 4 records from Flora d'Andorra. 4 records from ArtenFinder. 223 records from Lund Botanical Museum (LD). 754 records from vegetation releves on grassland gridplots 2007-2009. 925 records from vegetation releves on grassland gridplots in 2007. 225 records from Norwegian Species Observation Service. 39 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 1 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 53 records from GenLink - Genetic diversity of Bromus hordeaceus. 3 records from Bernice P. Bishop Museum. 340 records from Carnet en Ligne. 33 records from Staffordshire Ecological Record - SER Species-based Surveys. 2 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 4 records from LNHG Biological Records Dataset. 1 records from English Nature Berkshire Staff Surveys 1990's. 194 records from Merseyside BioBank (verified). 2 records from Vascular plant diversity in forests. 1135 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 9 records from Vascular plant herbarium, Tromsø Museum. 117 records from Vascular plant herbarium, NTNU University Museum. 259 records from Données ONF Faune-Flore-FOnge. 7 records from New Zealand Biodiversity Recording Network. 704 records from Vascular Plants, Field notes, Oslo (O). 3 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2737 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 1918 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 47 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 1 records from Ecofact. 8 records from Plants, herbivores and their natural enemies along a grassland management gradient 2008. 1 records from Green Plant Herbarium (TRT). 519 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 8 records from Miscellaneous Vascular Plants. 1858 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 21 records from Allan Herbarium (CHR). 4 records from Herbarium of University of Białystok - Vascular Plants. 4 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 7 records from Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 10 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 2 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 430 records from Vascular Plant Herbarium, Oslo (O). 169 records from Local Wildlife Site Surveys Oxfordshire. 26529 records from Flora von Deutschland (Phanerogamen). 26 records from Vascular plants of Amrum 2007-2008. 3877 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from E. C. Smith Herbarium (ACAD). 1 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 89 records from National Trust for Scotland Species Records. 8 records from Vascular plant field notes, NTNU University Museum. 11 records from Vascular plants in Danish coastal meadows. 1 records from SysTax - Herbaria. 22 records from Geneva Herbarium – General Collection (G). 9 records from English Nature and NCC Oxfordshire Surveys. 61 records from Instituto de Botánica Darwinion. 15 records from Nijmegen Natural History Museum (NL) - Herbarium. 2319 records from BRERC species records within last 15 years. 14 records from Flora of the Stołowe Mts.. 75 records from CAS Botany (BOT). 155 records from Atlas des plantes vasculaires de Lorraine. 1 records from 2003-2004 Wokingham WHS Surveys. 7 records from NCC Berkshire Grassland Survey 1984-1987. 140 records from Vegetation releves in 150 grassland EPs in 2008. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences